Medical Cannabis Availability and Mental Health: Evidence from New York's Medical Cannabis Program - Coleman Drake; Dylan Nagy; David Slusky; Matthew Eisenberg (Institute of Labor Economics (IZA), 2024)
Evidence on cannabis legalization's effects on mental health remains scarce, despite both rapid increases in cannabis use and an ongoing mental health crisis in the United States. We use granular geographic data to estimate medical cannabis dispensary availability's effects on self-reported mental health in New York state from 2011 through 2021 using a two-stage difference-in-differences approach to minimize bias introduced from the staggered opening of dispensaries. Our findings rule out that medical cannabis availability had negative effects on mental health for the adult population overall. We also find that medical cannabis availability reduced past-month self-reported poor mental health days by nearly 10%—3.37 percentage points—among adults 65 and above. These results suggest medical cannabis access has positive health impacts for older populations, likely through pain relief.
Keywords: H75; I12; I18; I31; K32; K42; 330; cannabis; mental health